Thermal reorganization of alkyl-substituted thienothiophene semiconductors. Issue 23 (9th May 2016) - Pozdin, Vladimir A.; Smilgies, Detlef-M.; Fong, Hon Hang; Sorensen, Michael; He, Mingqian
Abstract : Controlling the structure of polymer thin films under thermal annealing is vital to realize reproducible transport properties and acceptable device lifetimes needed to fabricate electronic circuits. Abstract : Controlling the structure of polymer thin films under thermal annealing is vital to realize reproducible transport properties and acceptable device lifetimes needed to fabricate electronic circuits. We investigated the behavior of two conjugated polymers with different length alkyl side-chains upon thermal annealing. The longer side-chain polymer showed greater stability with no significant reorganization upon annealing. The shorter side-chain polymer underwent conformation changes upon thermal annealing, which cannot be explained by residual solvent effects, a liquid crystal phase transition, or side-chain melting. Using an in situ study of thermal annealing we can attribute the film reorganization to changes in the side-chain tilt, which result in a positive linear expansion coefficient on the order of 8 × 10 −4 K −1 . Neither polymer features phase transitions above room temperature nor exhibited significant or abrupt changes during thermal processing, which is a mandatory property for the manufacture of flexible electronics.